STUDENT-WRITERS CLAIMS IN HORTATORY ARGUMENTATIVE ESSAYS: AN APPRAISAL STUDY IN CONVENIENCE WRITING - Wihadi, Marwito; Sujatna, Eva Tuckyta Sari; Soeriasoemantri, Ypsi; Karlieni, Eni (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
Working on writing argumentative essay instructions has been practices in a non-formal language learning settings. Yet, its students pursued claims are not fully explored as an evaluativion of how student-writers interact as conveying arguments with the readers. Investigating the linguistic resources on which they develop and evaluate these, two selected English Language essays were looked into regarding to exploitation of macrostructures in them. Subsequently, they were captured within the framework of appraisal theory as to emerge various trends relative to the employment of engagement resource types, combined with the other resources in confirming claims: graduation and attitudinal ones. It was pinpointed that the essays were low-graded notifying substantial numbers of monoglossic resources with low-considered attitudinal items. They failed to recognise other voices and alternative positions. Their construction of evaluative meanings provided feedbacks, enhancing classroom teachers awareness of typical features in genre-based instructions.